Validity of the Kessler Psychological Distress scale in Brazilian higher education students - Jaqueline Galdino Albuquerque Perrelli; Gabriel Vinícius Souza de Vasconcelos; Jéssica Rodrigues Correia e Sá; Pollyanna Fausta Pimentel de Medeiros; Roberta Uchôa; Zila Sanchez (Revista Latino-Americana de Enfermagem)
Objective: to evaluate of the validity of the Brazilian version of the Kessler Psychological Distress Scale, based on its internal structure, concurrent validity, and predictive validity, for the screening of psychological distress among higher education students. Method: methodological study with 1,034 participants, using the Kessler Psychological Distress Scale as well as the Self-Reporting Questionnaire. An analysis of the internal structure was conducted using a two-factor confirmatory factor analysis, which evaluated fit indices and hierarchical omega reliability coefficients. A Pearson’s correlation test was used to assess concurrent validity, while sensitivity, specificity, areas under the ROC curve and 95% confidence intervals were used to assess predictive validity. Results: the bifactor model demonstrated excellent fit indices (CFI=1.000; TLI=0.999; SRMR=0.019; RMSEA=0.028; 95%CI: 0.015 - 0.041) as well as high reliability (ωH=0.886). It was observed that there was a strong correlation between the K10 and the SRQ (r=0.813; 95%CI: 0.784 - 0.837). The ideal cut-off point for screening was identified as being higher than 21, with a sensitivity of 85.2% and a specificity of 82.9%. Conclusion: the structure composed of a general factor, psychological distress, demonstrated a high level of reliability. The scale demonstrated concurrent and predictive validity for the assessment of psychological distress among university students.